Redescripción de Parodon caliensis y Saccodon dariensis (Characiformes: Parodontidae) - Londoño-Burbano, Alejandro (Universidad de Costa Rica, 2010)
Redescription of Parodon caliensis and Saccodon dariensis (Characiformes: Parodontidae). Parodontidae family is a group of Characiformes fishes distributed throughout South America and parts of Panama, except in the basins of the southern Bahia state in Brasil on the Atlantic coast, Patagonia and the Amazon river channel. The family includes three genera: Apareiodon Eigenmann 1916, Parodon Valenciennes 1849 y Saccodon Kner 1863, 28 recognized species and two valid genera: Parodon and Saccodon. Redescription of Parodon caliensis and Saccodon dariensis is carried out based on type, and topotypic material from Colombia. Significant differences were found in morphometric, meristic, osteologic and color characters. S. dariensis is widely distributed but P. caliensis is restricted to the upper Cauca River drainage. Three species are considered herein as synonyms of S. dariensis: Apareiodon dariensis, A. compressus and S. caucae. Sexual dimorphism is described for both species. Rev. Biol. Trop. 58 (3): 813-826. Epub 2010 September 01.